Multilocation Yield Trials and Yield Stability Evaluation by GGE Biplot Analysis of Promising Large-Seeded Peanut Lines - Pobkhunthod, Nipatcha; Authapun, Jetsada; Chotchutima, Songyos; Rungmekarat, Sarawut; Kittipadakul, Piya; Duangpatra, Jaungjun; Chaisan, Tanapon (Frontiers in Genetics, 2022)
The demand by industries for large-seeded peanuts is increasing in Thailand and Southeast Asia. New large-seeded peanut lines were recently developed in Thailand to respond to the demand. In this study, a multi-location yield trial was performed to identify the best genotype(s) in Thailand's central region and investigate the genotype × environment interaction (GEI) on peanut production. Twelve promising large-seeded peanut lines and two check varieties (KU50 and KK6) were planted at 12 different planting locations during the dry and rainy seasons of 2018 and 2019. This study found significant yield potential variability in the promising lines of peanuts evaluated at the different planting locations. A combined analysis of variance presented that environment and genotypes had a considerable impact (P<0.001) on pod and seed yield. The GEI showed a high impact (P<0.01) on pod yield and an effect (P<0.05) on seed yield. The environment presented the most significant influence on pod and seed yield variations, followed by genetics and GEI. The total variation in seed yield was 64.22%, composed of PC1 and PC2 values at 45.71% and 18.51%. GGE biplot analysis of the yield potentials at each location indicated that KUP12BS029-1-1-3 was the ideal genotype, with high yield potential and most stability at multi-locations, followed by KUP12BS030-3-4-1 and KUP12BS030-1-4-3. These promising lines will be released as new peanut varieties in central Thailand and recommended as parental lines in breeding programs for large-seeded and yield potential in Thailand and Southeast Asia.